Is Asia Decoupling from the United States (Again)?. (1st August 2013) - Leduc, Sylvain; Spiegel, Mark M.
Abstract: The recovery from the recent global financial crisis exhibited a decline in the synchronization of Asian output with the rest of the world. However, a simple model based on output gaps demonstrates that the decline in business cycle synchronization during the recovery from the global financial crisis was exceptionally steep by historical standards. We posit two potential reasons for this exceptionally steep decline. First, financial markets during this recovery improved from particularly distressed conditions relative to previous downturns. Second, monetary policy during the recovery from the crisis was constrained in developed economies by the zero bound, but less so in Asia. To test these potential explanations, we examine the implications of an increase in corporate bond spreads similar to that which took place during the recent European financial crisis in a three‐region open‐economy dynamic stochastic general equilibrium model. Our results confirm that global business cycle synchronization is reduced when zero‐bound constraints across the world differ. However, we find that the impact of reduced financial contagion actually goes modestly against our predictions.